The role of production site isolation in the plant health situation of sweet chestnut (Castanea sativa) - Kovács, Gabriella; Radócz, László (Acta Agraria Debreceniensis, 2017)
The most destructive pathogen for the European chestnut is the blight fungus Cryphonectria parasitica (Murr.) Barr. The spread of the fungus was very fast in Europe within a few decades in the second half of the past century. During the tree-health checking in the chestnut andwalnut plantation in Romania, Hargita county, next to Homoródkarácsonyfalva village, we especially concentraded on the signs of blight disease occurrence. The grove is laying on a western slope, under a pine forest. This favourable geographical space protects it not only from pathogen attacts, but it has a special, mild microclimate for nut and chestnut trees. The European chestnut could be a valuable member of local forests, opening a new perspective under conditions of climate changes.